Effect of Poverty on Services Export Concentration in Developing Countries - Sèna Kimm Gnangnon (ZBW – Leibniz Information Centre for Economics, 2020)
This paper investigates the effect of poverty on services export concentration in developing countries. The analysis has used an unbalanced panel dataset of 98 developing countries over the period 1995-2014. Findings suggest that a higher poverty rate is positively associated services export concentration, and this effect translates through three channels, namely the education level (a proxy for human capital), the degree of trade policy liberalization (and trade openness), and the level of export product concentration. Thus, if they were to diversify services export items, policymakers should implement policies that directly promote services export diversification (such as liberalizing trade, including reducing services trade barriers, and improving the business environment), but also measures and policies that directly target poor segments of the population.
Keywords: F14; O11; I32; 330; Poverty; Services export concentration; Education; Trade policy liberalization; Trade Openness; Export product concentration